2016
DOI: 10.1590/s0100-736x2016001000012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiológico e avaliação de fatores de risco da infecção por Toxoplasma gondii e achados clinico-patológicos da infecção aguda em cães admitidos em um Hospital Escola Veterinário

Abstract: RESUMO.-Esse trabalho teve como objetivo estudar a prevalência e respectivos fatores de risco para infecção do Toxoplasma gondii em cães provenientes de uma população We aimed to verify the prevalence and risk factors for Toxoplasma gondii infection in dogs addimitted at the hospital. We also assessed the occurrence rates and the clinical and pathological repercussion of the acute infection by T. gondii in these animals. Antibodies were detected in 7% (26/386) of a population of 386 dogs of both genders and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the present study, most seropositive dogs had low antibody titers detected by IFAT (53.7% at 1:16). This profile was also reported by Strital et al [79] in dogs attended at the Veterinary School Hospital of the University of Mato Grosso (1:16-46%), by Brasil [9] in domiciled dogs attended at 34 veterinary clinics in Paraíba (1:16-35.1%), both in Brazil and by Hosseininejad et al [38], in domiciled and stray dogs in Iran (1:16-42.7%). In relation to the seropositive cats detected in this study, the titration most frequently observed in IFAT was 1:64 (59.1%).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In the present study, most seropositive dogs had low antibody titers detected by IFAT (53.7% at 1:16). This profile was also reported by Strital et al [79] in dogs attended at the Veterinary School Hospital of the University of Mato Grosso (1:16-46%), by Brasil [9] in domiciled dogs attended at 34 veterinary clinics in Paraíba (1:16-35.1%), both in Brazil and by Hosseininejad et al [38], in domiciled and stray dogs in Iran (1:16-42.7%). In relation to the seropositive cats detected in this study, the titration most frequently observed in IFAT was 1:64 (59.1%).…”
Section: Discussionsupporting
confidence: 77%
“…Also, the consumption of homemade food was associated with greater exposure to the protozoan only in the feline population. The consumption of raw meat, offal and leftover homemade food was also associated with seropositivity for T. gondii in other populations of domiciled dogs and cats in Brazil and in other countries [10,13,54,75,79]. This result indicates that the exposure of domiciled dogs and cats to T. gondii occurs in the home environment through the supply of these foods by the owners.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations